Complete mitochondrial genome of the house bat Pipistrellus abramus (Mammalia: Chiroptera) from Korea. Issue 2 (2nd January 2017) - Kim, Ji Young; Kim, Hye Ri; Lim, Sang Jin; Kim, Hyun Ju; Cho, Jae Youl; Park, Yung Chul
Abstract: We determined and annotated the complete mitogenome of the house bat Pipistrellus abramus (Chiroptera: Vespertilionidae) from Korea. The complete mitogenome is a circular molecule of 17, 236 bp in length, including 13 protein-coding genes, 2 ribosomal RNA genes, 22 transfer RNA genes, and 2 non-coding regions (L-strand replication origin and control region). The mitogenome is AT-biased, with a nucleotide composition of 33.7% A, 29.9% T, 23.2% C, and 13.2% G. The phylogenetic analysis revealed that the house bat P. abramus from Korea is well grouped with that from Japan and placed within the genus Pipistrellus clade, which has the noctule bat Nyctalus as sister clade.